Probing N-glycoprotein microheterogeneity by lectin affinity purification-mass spectrometry analysis. Issue 19 (25th April 2019) - Wu, Di; Li, Jingwen; Struwe, Weston B.; Robinson, Carol V.
Abstract : A lectin affinity purification-mass spectrometry approach to characterize lectin-reactive glycoproteoforms and elucidate lectin specificities at the intact protein level. Abstract : Lectins are carbohydrate binding proteins that recognize specific epitopes present on target glycoproteins. Changes in lectin-reactive carbohydrate repertoires are related to many biological signaling pathways and recognized as hallmarks of several pathological processes. Consequently, lectins are valuable probes, commonly used for examining glycoprotein structural and functional microheterogeneity. However, the molecular interactions between a given lectin and its preferred glycoproteoforms are largely unknown due to the inherent complexity and limitations of methods used to investigate intact glycoproteins. Here, we apply a lectin-affinity purification procedure coupled with native mass spectrometry to characterize lectin-reactive glycoproteoforms at the intact protein level. We investigate the interactions between the highly fucosylated and highly branched glycoproteoforms of haptoglobin and α1-acid glycoprotein using two different lectins Aleuria aurantia lectin (AAL) and Phaseolus vulgaris leucoagglutinin (PHA-L), respectively. Firstly we show a co-occurrence of fucosylation and N -glycan branching on haptoglobin, particularly among highly fucosylated glycoproteoforms. Secondly, we analyze the global heterogeneity of highly branched glycoproteoforms of haptoglobin and α1-acid glycoprotein and reveal that while multi-fucosylation attenuates the lectin PHA-L binding to haptoglobin, it has no impact on AGP. Taken together, our lectin affinity purification native MS approach elucidates lectin specificities between intact glycoproteins, not achievable by other methods. Moreover, since aberrant glycosylation of Hp and AGP are potential markers for many diseases, including pancreatic, hepatic and ovarian cancers, understanding their interactions with lectins will help the development of carbohydrate-centric monitoring methods to understand their pathophysiological implications.